Peningkatan Kesadaran Masyarakat dalam Pemilahan Sampah melalui Sosialisasi dan Pembangunan Sarana Prasarana Tempat Sampah - Wulandari, Suci; Waspodo Dias Adrianto, Angger; Teguh Pramono, Dwi; Riska Sebastian, Yoanna (PT. Artha Genetikalab Indonesia, 2025)
Waste management is a major challenge in coastal tourism areas, including Pantai Kembar Terpadu, Puring Subdistrict, Kebumen Regency, Central Java. One of the implemented innovations is the provision of 47 waste sorting bins, divided into three categories: organic, inorganic, and hazardous and toxic materials (B3). This study aims to describe the implementation of the waste sorting bins program as a community-based environmental conservation effort. The research applied a descriptive qualitative approach through field observations, recording the distribution of bins, and interviews with vendors and site managers. The results show that 47 waste sorting points were distributed to 56 front stalls, 40 back stalls, and 26 street vendors. The implementation of sorted bins is expected to reduce mixed waste volume, raise tourist awareness, and support Pantai Kembar Terpadu’s image as an eco-friendly tourism destination. The conclusion emphasizes that providing waste management facilities is a strategic step toward sustainable tourism development.